The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/09588221.2015.1068815
|View full text |Cite
|
Sign up to set email alerts
|

Switching perspectives: from a language teacher to a designer of language learning with new technologies

Abstract: Abstract. Despite abundant research on educational technology and strategic input in the field, various surveys have shown that (language) teachers do not seem to embrace in their teaching the full potential of information and communication technology available in our everyday life. Language students soon entering the professional field could accelerate the process, which highlights the role of teacher education in contributing to the change. The students should see how technology-development may change the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Our interdisciplinary research group has organized a number of digital technology development projects with children (see Iivari et al, ; Iivari & Kinnula, ; Iivari & Kinnula, ; Kinnula, Laari‐Salmela, & Iivari, ; Kuure et al, ; Kuure, Halkola, Iivari, Kinnula, & Molin‐Juustila, ; Molin‐Juustila, Kinnula, Iivari, Kuure, & Halkola, ). Five of the six presented studies have been conducted in the context of Finnish schools.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our interdisciplinary research group has organized a number of digital technology development projects with children (see Iivari et al, ; Iivari & Kinnula, ; Iivari & Kinnula, ; Kinnula, Laari‐Salmela, & Iivari, ; Kuure et al, ; Kuure, Halkola, Iivari, Kinnula, & Molin‐Juustila, ; Molin‐Juustila, Kinnula, Iivari, Kuure, & Halkola, ). Five of the six presented studies have been conducted in the context of Finnish schools.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite financial and pedagogic input as well as abundant research in the field, no great changes seem to have taken place in schools yet on a wider scale (OECD, ; European Union, ). Opportunities for children to take an active role in shaping their own technology‐rich environment have been scarce, despite the participatory and learner‐centred approaches used in digital education curricula (Kuure et al, ). For teachers and student teachers, it seems to be difficult to change practices and get pupils to envision future technologies collaboratively (Kuure et al, ).…”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…A team from the University of Oulu in Finland, for example, found that, when provided the opportunity to work as CALL designers to develop and implement their own materials, student-teachers may still have difficulty viewing themselves as future CALL designers [5]. The authors argue that since the role of a CALL teacher-designer is not yet clear to future teachers, it should therefore be more clearly established; it is critical for potential teacher designers to feel like they can be worthy participants in CALL material development.…”
Section: Introductionmentioning
confidence: 99%